Association Between Amyloid Accumulation and Sleep in Patients With Idiopathic REM Sleep Behavior Disorder - Lee, Hanul; Cho, Hyunjin; Choe, Yeong Sim; Seo, Sang Won; Joo, Eun Yeon (Frontiers in Neurology, 2020)
Background and Objectives: Amyloid-beta protein may lead to sleep disturbance and eventually develop cognitive impairment. Idiopathic rapid eye movement (REM) sleep behavior disorder (iRBD) is a predictor of neurodegeneration, yet there have been limited studies evaluating the relationship between cognitive decline and amyloid accumulation in iRBD patients. To investigate the clinical and sleep characteristics of iRBD patients and its association with amyloid deposition, Methods: We enroll 23 iRBD patients (mean age 65.8 y, male 73.9%) and their mean history of clinically suspected RBD was 6.5y. All underwent 18F-flutemetamol amyloid PET completed polysomnography (PSG) and questionnaires. Patients were classified into two groups according to amyloid deposition as amyloid positive and negative. Clinical and sleep parameters were compared between groups and were correlated with amyloid deposition, calculated as a standardized uptake value ratio (SUVR). Results: Four patients (17.4%) were revealed to be amyloid positive and they showed increased percentage of wake after sleep onset (WASO), stage N1, and stage N2 sleep and worse on the Stroop Word Color Test compared to amyloid negative patients. Global SUVR was correlated with total sleep time, sleep efficiency, WASO, and N1 sleep and these sleep parameters were associated with a part of default mode network of brains such as orbitofrontal, dorsolateral prefrontal, and left temporal areas. Conclusion: iRBD patients with amyloid deposition have worse sleep quality than patients without amyloid. Relationship between fragmented sleep and amyloid deposition in the default mode network may be crucial to elucidate the disease progress of iRBD.